Timor-Leste Workforce Development : SABER Country Report 2013 - World Bank (Washington, DC, 2014)
Timor-Leste, a young country with a young population, has enjoyed rapid growth driven by a booming oil sector. However, the country still faces significant challenges such as a high poverty rate, a lack of infrastructure, high levels of unemployment among the youth and critical human resource constraints. The skills shortage has been felt throughout the economy, starting with the oil and gas sector where a large proportion of workers are foreign. Developing a skilled workforce is a necessary step to stimulate the incipient private sector and attract foreign investment.